FAKTOR YURIDIS YANG MEMPENGARUHI PENAMBAHAN JUMLAH DAFTAR PEMILIH KHUSUS PADA PEMILU 2019 DI KABUPATEN TULUNGAGUNG - Shobahah, Nurush; Rifai, Much Anam (Ahkam: Jurnal Hukum Islam, 2020)
The relatively high number of Registered Special Voters in the 2019 Election became a problem. Since Registered Special Voters are people who qualifi as voters but they are not listed in the Registered Fixed Voters, it can be concluded that the voter registration conducted by General Election Comission is not as qualifying as it should be. However, there is an opinion that basically Registered Special Voters are not pure as it is listed. Some voters have already been registered as Registered Fixed Voters. Through this qualitative descriptive research with a case-approach, the research purpose is to reveal factors making people as Registered Special Voters in Tulungagung Regency. The result was that there were 23 percent of voters in the Registered Special Voters in Tulungagung who were already registered as Registered Fixed Voters. They are registered as Registered Special Voters presumably due to the following factors: First, problem arised when voters are mistakenly put in the polling station. Second, problem due to administrative error in recording the presence of the voters. Third, problem caused by the residence exchange. In order to solve this problem, electoral regulation reconstruction is needed, especially in relation to updating registered voter and/or voting-count mechanisme. Keywords: Election, Registered Special Voters, Reconstructing Regulation.